1994
DOI: 10.1182/blood.v83.3.749.749
|View full text |Cite
|
Sign up to set email alerts
|

Plasma zinc level and thymic hormone activity in young cancer patients

Abstract: It has been reported that in many neoplastic diseases, including leukemia, alterations in plasma zinc levels may frequently occur, although the causes for such alterations have yet to be clearly defined. Since zinc is required to induce biological activity to thymulin (Zn-FTS), a biochemical defined thymic hormone, and marginal zinc deficiencies may prevent its peripheral biological activation, we investigated the plasma level of zinc and of both active thymulin (Zn- FTS) and total zinc saturable thymulin (Zn-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…An explanation for this finding could reside on the insufficient zinc bridges that are important for sperm chromatin stabilization (Bjorndahl and Kvist, 2009). Interestingly, it has been reported that there are low levels of cellular zinc in patients with head and neck cancers (Prasad et al, 2009) and low levels of plasma zinc in young patients with lymphoblastic leukemia (Mocchegiani et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…An explanation for this finding could reside on the insufficient zinc bridges that are important for sperm chromatin stabilization (Bjorndahl and Kvist, 2009). Interestingly, it has been reported that there are low levels of cellular zinc in patients with head and neck cancers (Prasad et al, 2009) and low levels of plasma zinc in young patients with lymphoblastic leukemia (Mocchegiani et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Thymulin represents an important parameter for evaluating thymic endocrine activity because it is secreted exclusively by thymic subcapsular and medullar cells [3]. As few reports present thymulin values for the normal population [13,16–18], especially for children under 1 year old, we detail a series of age‐related thymulin titres in a healthy population throughout the course of life. We demonstrate that thymulin is already detectable at birth.…”
Section: Discussionmentioning
confidence: 99%
“…All cultures were performed in quadruplicate. The results, referring to the highest responses regardless of the mitogen concentration used, are expressed as counts per minute (cpm) per culture 37) .…”
Section: Lymphocyte Proliferative Responsementioning
confidence: 99%